Solve the equation for the requested variables. \( x(c w+q)=v+f \) Solve for \( \mathrm{x}: x= \) Solve for w: \( w= \) entry tip: if you have several parts to a numerator or denominator, put them in parenthesis. To enter \( \frac{2 x}{a+b} \) we type " \( (2 x) /(a+b)^{-} \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To solve for \( x \) in the equation \( x(c w + q) = v + f \), we isolate \( x \) by dividing both sides by \( (c w + q) \). Thus, we have: \[ x = \frac{v + f}{c w + q} \] To solve for \( w \), we need to rearrange the equation. First, we move \( v + f \) to one side: \[ x(c w + q) = v + f \] Now, divide both sides by \( x \): \[ c w + q = \frac{v + f}{x} \] Then, isolate \( w \): \[ c w = \frac{v + f}{x} - q \] \[ w = \frac{\frac{v + f}{x} - q}{c} \] So, the solutions are: \[ x = \frac{v + f}{c w + q} \] \[ w = \frac{\frac{v + f}{x} - q}{c} \]